Implementation of Reading Aloud Methods to Improve Early Reading Skills: A Case Study Analysis in Elementary School - Ningsih, Srihandayani; Winarni, Retno; Rukayah, Rukayah (Journal of Basic Education Research, 2025)
Purpose of the study: This study aims to examine the implementation of the reading aloud method to improve early reading skills among first-grade students at public alementary school 1 Talesan. The focus includes the instructional process, student responses, skill development, and challenges faced during the intervention. Methodology: This research used a qualitative approach with a case study design. Data were collected using observation sheets, semi-structured interviews, and documentation analysis. The study involved one Grade I teacher and 19 students. Data were analyzed using Miles and Huberman’s interactive model, and data validation employed triangulation of sources and techniques. Main Findings: The reading aloud method significantly improved students' prosodic reading skills, particularly intonation and vocal clarity. Students demonstrated increased participation and reading confidence. Challenges included varied reading proficiency levels and limited instructional time, which were mitigated through adaptive strategies such as visual aids and individual mentoring. Novelty/Originality of this study: This study presents a contextualized model for implementing the reading aloud method in early-grade classrooms using socio-emotional scaffolding. The findings contribute new insights into integrating expressive reading with adaptive teaching to enhance early literacy in post-pandemic learning environments.